2003
DOI: 10.1136/pmj.79.931.279
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of bone mineral density, calcium, and vitamin D status in the Gujarati and white populations of Leicester

Abstract: Objectives: To evaluate differences in bone mineral density (BMD), calcium, and vitamin D status between the Gujarati (South Asian) and white populations resident in Leicester and to determine whether this was linked to lifestyle factors. Design: An observational cross sectional study of randomly selected Gujarati and white volunteers aged from 20-40 years. Setting: City of Leicester. Participants: Subjects were randomly selected by age (20-40 years) and ethnicity. A total of 262 individuals volunteered to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 9 publications
(7 reference statements)
4
28
0
Order By: Relevance
“…Strong positive correlation of BMI with BMD at all sites and negative correlation with PTH, ALP, and phosphates seen in the present study was also observed by several other workers [6,7,39]. There was no significant correlation observed between serum 25(OH)D and BMD at different sites which is in concordance with our earlier studies [8-11, 13, 32].…”
Section: Calcaneum Bmdsupporting
confidence: 94%
“…Strong positive correlation of BMI with BMD at all sites and negative correlation with PTH, ALP, and phosphates seen in the present study was also observed by several other workers [6,7,39]. There was no significant correlation observed between serum 25(OH)D and BMD at different sites which is in concordance with our earlier studies [8-11, 13, 32].…”
Section: Calcaneum Bmdsupporting
confidence: 94%
“…However, overall the recent results suggests that there is a still high burden of relatively low vitamin D levels in the South Asian general population and is similar to other reports (Ford et al, 2006;Hamson et al, 2003;Hull et al, 2010).…”
Section: Resultssupporting
confidence: 90%
“…Migrant South Asians living in the UK have among the highest rates of VDD (Ford et al, 2006;Hamson et al, 2003;Hull et al, 2010). Pilot data South Asians also have a high prevalence of T2DM and it is plausible that this relates directly to sub-optimal Vitamin D status (Boucher et al, 2006).…”
Section: South Asians and Vddmentioning
confidence: 99%
“…Only 10% of the women and 8% of the men with Pakistani background had s-25(OH)D of 50 nmol/l or more, compared to 86% of men and women with Norwegian background. A high prevalence of vitamin D deficiency among immigrants has also been reported in other Northern European countries, such as Denmark (Glerup et al, 2000;Pedersen et al, 2003) and the UK (Shaw & Pal, 2002;Hamson et al, 2003). However, the evidence is limited and the preponderance of studies are not populationbased but conducted in clinical settings.…”
Section: Introductionmentioning
confidence: 96%